HR practices through the lens of technology and digital transformation - Edisa Dreković; Marija Radosavljević; Žaklina Teofilović (Economic Themes, 2023)
The company's digital transformation requires the optimization and automation of processes through Industry 4.0 technology, leading to a new business model. Along with technology, effective human resource management (HRM) is crucial for this model. HRM and Industry 4.0 technology are interdependent. Technologies require new HR operating models, and HR, through organizational management strategies such as change management, agile organizations, and talent management, influences the provision of a workforce capable of implementing these disruptive technologies. This paper focuses on HR's role in digital transformation and the resulting changes in HRM and HR practices. It presents use cases of Industry 4.0 technology and their benefits. The study presented in this paper examines the impact of HR practices on operational, financial, and employee performance in relation to the use of disruptive technologies. A survey questionnaire was used to examine this impact on 11 large and medium-sized companies in Serbia, using statistical methods of descriptive statistics and correlation analysis through SPSS 23 software to analyze the results. The research showed that the use of artificial intelligence and machine learning (AI/ML) in HR processes has a positive effect on employee performance, as well as operational and financial performance. Other hypotheses were only partially proven. The research also revealed the lack of training for HR employees regarding the use of digital technologies in HR processes and digital skills compared to other sectors in the company. The recommendation is that HR managers begin training on the digitization of HRM as soon as possible.
Keywords: M15; O15; C83; 330; HR; digital transformation; VR/AR; AL/ML; cloud computing; IoT; people analytics; gamification